2023
DOI: 10.5334/bc.304
|View full text |Cite
|
Sign up to set email alerts
|

Achieving deep-energy retrofits for households in energy poverty

Abstract: Climate change and energy poverty are two sustainability challenges that can be addressed through deep-energy retrofits for homes. This systematic review identifies which factors influence the achievement of energy retrofits for households vulnerable to energy poverty. It covers both energy-poor households and the landlords or building owners of energy-poor households. The results identify a range of influential factors across several themes: financial, policy and organizational, trust and communication, techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…To reduce energy poverty, the results showed that a deep renovation is necessary, in line with the findings of Tozer, MacRae and Smit [33]. With the current high energy prices, only a deep renovation results in a ratio of the cost for heating compared to the income of around 5%, which is in line with the situation of the unrenovated building before the energy crisis.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…To reduce energy poverty, the results showed that a deep renovation is necessary, in line with the findings of Tozer, MacRae and Smit [33]. With the current high energy prices, only a deep renovation results in a ratio of the cost for heating compared to the income of around 5%, which is in line with the situation of the unrenovated building before the energy crisis.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…Based on the results for the income of the SHCs and the costs for the tenants with low income, the first alternative economic model, with a limited cost of living based on the incomes, seems to be most interesting as this is most beneficial for the tenants and results in a higher income for the SHCs compared to the current model. The selection of an alternative economic model that is beneficial for both the housing association and the tenants is supported by the findings of Tozer, MacRae and Smit [33], who claim that access to low-or no-cost retrofit options alongside tenant protection mechanisms would make energy retrofit policies aimed at vulnerable households more effective. Adapting the current economic model to the more service-based 'COL 2.5%' model is in line with the findings of Bouzarovski and Petrova, who mention, amongst other suggestions, that widening energy poverty amelioration frameworks towards 'services' might enable a form of public engagement, where the tenants can participate in the utility provision [13].…”
Section: Conclusion and Discussionmentioning
confidence: 96%
See 1 more Smart Citation